Pemetaan Daerah Rawan Banjir Dengan Menggunakan Metode Weighted Overlay Studi Kasus Kota Malang - Yulaichah; Kurniawan, Andri; Hizbaron, Dyah Rahmawati (JPIG (Jurnal Pendidikan dan Ilmu Geografi), 2025)
Malang City is one of the regions in Indonesia with significant flood risk due to a combination of natural factors and human activities. This study aims to map flood-prone areas using Geographic Information System (GIS) technology by considering six main parameters: slope, elevation, rainfall, soil type, land use, and river buffer. Using the weighted overlay method, the flood risk zoning map is classified into three categories: low, medium, and high. The results show that 67.22% of Malang City falls under the high-risk category, particularly in Klojen, Blimbing, Sukun, and Lowokwaru districts. Dominant factors contributing to flood vulnerability include high rainfall, dense settlements, and a lack of green spaces. The study recommends mitigation measures such as improving drainage systems, increasing green areas, and implementing risk-based spatial planning to minimize flood impacts. The flood risk zoning map serves as a crucial tool for the government to plan and manage floods more effectively.